Is STEM learning can significantly effect students’ sustainability awareness? - Rahmadayanti, Annesha; Widodo, Ari; Riandi, Riandi (JURNAL BIOEDUKATIKA, 2024)
Sustainable awareness is one of the things that individual should possess as a form of concern for the enviroment. This research aims to analyze how the STEM learning model influences students’ sustainable awareness. The study was conducted at one of  Madrasah Aliyah (MA) Kota Bengkulu for 10th grade student. This reseach utilized a quasi-experimental method whith a pretest-postest non-equivalent control group design. The sample fot this study consisted of 10th grade students, with two control clasess and two experiment clasess which selected using convinience sampling technique. The research incoporates both qualitative and quantitave data. The qualitative data in this study consists of unstructured interviews results, which are utilized to strengthen the reseach data. The quantitve data includes pre-test and post-test scores processed using SPSS. The research results indicate a non-significant influence of the STEM learning model on students’ sustainable awareness (sig. 0.144>0.05). There are three indicators of sustainable awareness used in this research, derived from the synthesis of several articles, however, one out of three indicators in sustainable awareness in this study shows a significant effect, specifically in the attitude awareness indicator (sig. 0.008<0.05). therefore, it can be concluded that STEM learning model in this study does not have significant impact on students’s sustainable awareness.